Impact of dietary inclusion of clinoptilolite as substitute of soybean meal on growth performance, dietary energetics and carcass traits of feedlot ewes fed a corn-based diet - Estrada-Angulo, Alfredo; Urías-Estrada, Jesús D; Castro-Pérez, Beatriz I; Contreras-Pérez, Germán; Angulo-Montoya, Claudio; Barreras, Alberto; López-Soto, María A; Olivas-Valdez, José A; Plascencia, Alejandro (Austral Journal of Veterinary Sciences, 2017)
Forty ewes (31.725±1.44 kg initial LW) were used to evaluate the effects of clinoptilolite (ZEOL) supplementation (0, 1, 2, and 3%, DM basis of diet) as substitute of soybean meal (SBM) in a finishing corn-based diet on growth performance, dietary energetics, and carcass traits. The experiment lasted 56 days. For each percentage of substitution of SBM by ZEOL, the crude protein and net energy (NE) of basal diet were decreased in 0.37 percentage units and 0.02 Mcal/kg, respectively. There were no treatment effects (P>0.27) on average daily gain (ADG), dry matter intake (DMI), and gain efficiency (ADG/DMI). Dietary NE was not affected by ZEOL supplementation (P≥0.69). However, due to the inertness (it does not provide energy) of ZEOL, itself, the ratio of observed-to-expected dietary NE linearly increased (P=0.02) and the ratio of observed-to-expected DMI linearly decreased (P=0.02) with ZEOL supplementation. Clinoptilolite supplementation linearly decreased fat thickness (P=0.02) and visceral fat (P=0.03) with no effects (P≥0.12) on other carcass measures or the organ tissue weights (as proportion of g/kg of empty body weight). Dilution of CP and dietary NE by substitution of SBM by zeolite up to 3% did not negatively affect growth performance and carcass traits. This result suggests that the inclusion of up to 3% of clinoptilolite in substitution of a high protein source (SBM) on finishing diets has a positive effect on the utilization of dietary energy.